2020
DOI: 10.1002/star.201900008
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐Friendly Synthesis of Hydrogels from Starch, Citric Acid, and Itaconic Acid: Swelling Capacity and Metal Chelation Properties

Abstract: In this study, eco‐friendly superabsorbent hydrogels are prepared by the grafting and crosslinking reactions of itaconic acid and citric acid with starch, using potassium persulfate as the free radical initiator. The structure and morphology of the hydrogels are studied using Fourier transform infrared spectroscopy, scanning electron microscopy, and thermogravimetric analysis. The effect of the citric acid to starch ratio on the swelling properties is evaluated, and it is found that equal parts of citric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…Wang & Wang, 42 where an anionic group and a polyglycol were also added. Besides, non-porous surfaces were also reported by Duquette et al 33 on a natural citrate-crosslinked starch-based hydrogel. Moreover, Yoon, Lee & Lim 43 reported that the retrogradation process in refrigeration (4°C) decreased its porosity, which improved the enzymatic resistance to hydrolysis by αamylases.…”
Section: Sem Analysismentioning
confidence: 55%
See 2 more Smart Citations
“…Wang & Wang, 42 where an anionic group and a polyglycol were also added. Besides, non-porous surfaces were also reported by Duquette et al 33 on a natural citrate-crosslinked starch-based hydrogel. Moreover, Yoon, Lee & Lim 43 reported that the retrogradation process in refrigeration (4°C) decreased its porosity, which improved the enzymatic resistance to hydrolysis by αamylases.…”
Section: Sem Analysismentioning
confidence: 55%
“…The presence of a new well-defined band due to carbonyl bond vibration was confirmed (C=O, 1721-1755 cm -1 ) by the extrapolation of FT-IR spectra of the hydrogels and the raw material (Figure 3), indicative of cross-linking starch-citrate in anionic hydrogels. 33,35,36 A higher vibration intensity was present in hydrogels within absorbance range of 500-1220 cm -1 due to the bending of C-OH and C-O bonds, related to the decrease in the semicrystalline zone after the gelatinization process. 27 Furthermore, a higher intensity band were presented at 1639 cm -1 in the control hydrogel, representative of the vibration of water retained in the amorphous zone of the starches.…”
Section: Fi-ir Tga/dtg and Ea Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a new well-defined band due to carbonyl bond vibration was confirmed (C=O, 1721-1755 cm -1 ) by the extrapolation of FT-IR spectra of the hydrogels and the raw material (Figure 3), which is indicative of the starch-citrate cross-linking in anionic hydrogels. 33,35,36 A higher vibration intensity was presented in hydrogels within absorbance range of 500-1220 cm -1 due to the bending of C-OH and C-O bonds, related to the decrease in the semicrystalline zone after the gelatinization process. 27 Furthermore, the control hydrogel showed a higher intensity band at 1639 cm -1 , representative of the vibration of the water retained in the amorphous zone of native starches.…”
Section: Fi-ir Tga/dtg and Ea Analysismentioning
confidence: 98%
“…The hydrothermal treatment at 90°C was a non-destructive process that allowed the gelatinization of the granules and subsequent formation of the starch-citrate. The synthesis was performed based on the effective citrate cross-linked hydrogels reported by Wu et al 30 and Duquette et al 33 Refrigerated storage (120h/5°C) maintained humidity and prevented abrupt rupture of the hydrogel allowing better stability in the natural retrogradation process (20-25°C),…”
Section: Synthesismentioning
confidence: 99%